2002
DOI: 10.4049/jimmunol.169.12.6743
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cγ2 Is Essential for Specific Functions of FcεR and FcγR

Abstract: Phospholipase Cγ2 (PLCγ2) plays a critical role in the functions of the B cell receptor in B cells and of the FcRγ chain-containing collagen receptor in platelets. Here we report that PLCγ2 is also expressed in mast cells and monocytes/macrophages and is activated by cross-linking of FcεR and FcγR. Although PLCγ2-deficient mice have normal development and numbers of mast cells and monocytes/macrophages, we demonstrate that PLCγ2 is essential for specific functions of FcεR and FcγR. While PLCγ2-deficient mast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 91 publications
(81 reference statements)
7
71
1
Order By: Relevance
“…The functional defects observed in mice deficient in PLC␥ 2 are not restricted to B cells but are also observed in platelets, natural killer cells, monocytes/macrophages, and mast cells (60,61 There was no effect, however, of activated Cdc42 on PLC␥ 1 activity upon reconstitution of the two purified proteins in a cell-free system (65). At first glance, these findings are not easily consistent with the findings reported here.…”
Section: Discussioncontrasting
confidence: 55%
“…The functional defects observed in mice deficient in PLC␥ 2 are not restricted to B cells but are also observed in platelets, natural killer cells, monocytes/macrophages, and mast cells (60,61 There was no effect, however, of activated Cdc42 on PLC␥ 1 activity upon reconstitution of the two purified proteins in a cell-free system (65). At first glance, these findings are not easily consistent with the findings reported here.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies indeed have shown that PLC␥2 deficiency affect cytokine secretion in monocytes (32). To differentiate between these two possibilities, we measured cytokine production by intracellular staining in PLC␥2-deficient NK cells following either anti-NKG2D or anti-NK1.1 mAbs stimulation.…”
Section: Nk Cells From Plc␥2 ϫ/ϫ Mice Fail To Generate Cytokines Andmentioning
confidence: 99%
“…In brief, 10 ϫ 10 6 purified NK cells were stimulated with soluble anti-NKG2D (20 g/ml) followed by cross-linking with 10 g of the appropriate secondary IgG Ab (Jackson ImmunoResearch Laboratories) per ml. After incubation at 37°C for 5 min, the cells were washed in PBS containing 10 mM Na 3 VO 4 , lysed in ice-cold lysis buffer, and immunoprecipitated with either anti-PLC ␥1 or anti-PLC␥2 Ab (32). The precipitates were subjected to 8% SDS-PAGE and transferred to nitrocellulose membranes.…”
Section: Immunoprecipitations and Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…The calcium response results from the recruitment and activation of PLC-γ1 and/or 2, depending on the cell type Wen et al, 2002). The recruitment of PLC-γ involves the interaction of one of its SH2 domain with phosphorylated Y136 on LAT, and the interaction with the adapter Gads which binds to phosphorylated LAT terminal tyrosines.…”
Section: Intracellular Propagation Of Fcr Signalsmentioning
confidence: 99%